Prediction and Management for Relapse of Type 1 Autoimmune Pancreatitis After Initial Steroid Treatment: A Long-Term Follow-up From China. Issue 9 (October 2018) - Xin, Lei; Meng, Qian-Qian; Hu, Liang-Hao; Lin, Han; Pan, Jun; Hao, Lu; Liu, Pei-Pei; Qian, Wei; Wang, Luo-Wei; Li, Zhao-Shen
Abstract : Objectives: This study aimed to investigate the frequency, predictors, and management of relapse of type 1 autoimmune pancreatitis (AIP) after steroid treatment. Methods: One hundred one patients with type 1 AIP receiving steroid as initial treatment were enrolled. Predictors were identified by multivariate analysis using Cox proportional hazards model. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were calculated. Results: Thirty-nine (41.1%) patients experienced relapse after steroid treatment during a median follow-up of 40 months. The cumulative rate of relapse reached a plateau at 57.6% (95% CI, 50.3%–64.9%) at 59 months. Without maintenance therapy (HR, 4.53; 95% CI, 1.35–15.17) and proximal bile duct involvement (HR, 2.10; 95% CI, 1.07–4.14) were identified as risk factors. Repeated steroid treatment with the same initial dose but longer induction and tapering duration was given to 87.2% patients with relapse and obtained response (97.1%) during a short-term follow-up (median, 19 months). Conclusions: Relapses are common in type 1 AIP after steroid treatment. Without maintenance therapy and proximal bile duct involvement were risk factors. Repeated steroid treatment with longer duration is effective for relapse.